Agency and author German literature beyond the bestseller list - Halverson, Rachel J. 1961-; Schaper, Benjamin 1988- (Berghahn Books, 2025)
"The image of the solitary author devoting days and nights to writing endless bestselling novels remains an insidious and largely unchallenged myth within German culture. In this exacting examination of the German publishing industry, Agency and Author addresses the financial reality sometimes eclipsed by this idea. Focusing on lesser-known German-language writers and their interactions with the Literaturbetrieb ("literary scene"), Agency and Author explores the ways authors assert creative agency in an increasingly 'eventized' literary marketplace. Ranging from the impacts of literary awards to media hate campaigns, this volume spotlights how profoundly the German literary landscape and our understanding of authorship is transforming."
Includes bibliographical references and index
Keywords: Literatur; Deutsch; German literature / 20th century / History and criticism; Authorship; Authors and publishers / Germany; Essays; Aufsatzsammlung